Elevated Alu retroelement copy number among workers exposed to diesel engine exhaust. (26th May 2021) - Wong, Jason Y.Y.; Cawthon, Richard; Dai, Yufei; Vermeulen, Roel; Bassig, Bryan A.; Hu, Wei; Duan, Huawei; Niu, Yong; Downward, George S.; Leng, Shuguang; Ji, Bu-Tian; Fu, Wei; et al.
Abstract : Background: Millions of workers worldwide are exposed to diesel engine exhaust (DEE), a known genotoxic carcinogen. Alu retroelements are repetitive DNA sequences that can multiply and compromise genomic stability. There is some evidence linking altered Alu repeats to cancer and elevated mortality risks. However, whether Alu repeats are influenced by environmental pollutants is unexplored. In an occupational setting with high DEE exposure levels, we investigated associations with Alu repeat copy number. Methods: A cross-sectional study of 54 male DEE-exposed workers from an engine testing facility and a comparison group of 55 male unexposed controls was conducted in China. Personal air samples were assessed for elemental carbon, a DEE surrogate, using NIOSH Method 5040. Quantitative PCR (qPCR) was used to measure Alu repeat copy number relative to albumin (Alb) single-gene copy number in leucocyte DNA. The unitless Alu/Alb ratio reflects the average quantity of Alu repeats per cell. Linear regression models adjusted for age and smoking status were used to estimate relations between DEE-exposed workers versus unexposed controls, DEE tertiles (6.1–39.0, 39.1–54.5 and 54.6–107.7 µg/m 3 ) and Alu/Alb ratio. Results: DEE-exposed workers had a higher average Alu/Alb ratio than the unexposed controls (p=0.03). Further, we found a positive exposure–response relationship (p=0.02). The Alu/Alb ratio was highest among workers exposed to the top tertile of DEE versus the unexposed controls (1.12±0.08 SD vs 1.06±0.07 SD, p=0.01). Conclusion: Our findings suggest that DEE exposure may contribute to genomic instability. Further investigations of environmental pollutants, Alu copy number and carcinogenesis are warranted.